Entrepreneurial Marketing and Performance of Small and Medium Enterprises in South Africa - Fatoki, Olawale (Journal of Reviews on Global Economics, 2019)
The study investigated the effect of entrepreneurial marketing (EM) on the performance of SMEs. Performance was measured using both organisational and personal criteria. The study utilised the quantitative research approach. The cross-sectional survey method was used for data collection. Data was collected from small business owners through the survey method. The self-administered questionnaire method was used to collect data from the participants. Convenience and snowball methods were used for sampling. Descriptive statistics and multiple regression were used for data analysis. The Cronbach's alpha was used as the measure of reliability. The results of this study showed significant positive relationships between some dimensions of EM and organisational and personal performance. Theoretically, the study linked EM to the personal performance of the owners of SMEs. Empirically, the study adds to the literature on the relationship between EM and the financial performance of SMEs. Practically, the study suggested recommendations that can improve EM by SMEs.